A numerical investigation of the plastic deformation at the spall edge for a roller bearing. (October 2017) - Liu, Jing; Shi, Zhifeng; Shao, Yimin
Abstract: A clear understanding of dynamic contact characteristics in roller bearings (RBs) is a primary task for vibration analysis of the machineries, especially in the presence of spall failures. This work presents a new dynamic modelling method for a RB with a spall on the races to predict the time-varying plastic deformation at the spall edge. An improved two-degree-of-freedom dynamic model is used to calculate vibrations of the RB. Effects of the spall length, spall edge radius, external radial load, and rotor speed on the dynamic impact force between the spall edge and roller, maximum contact stress at the spall edge, total contact deformation between the spall edge and roller, plastic deformation at the spall edge, and spall edge propagation rate are analyzed. The proposed method is validated by a finite element (FE) method. The numerical results illustrate that the spall edge shape, external radial load, and rotor speed have a significant influence on the dynamic impact force, maximum contact stress, total contact deformation, plastic deformation, and spall edge propagation rate. This paper provides a greater understanding of the effects of the spall sizes and the spall edge shape on the contact characteristics and the vibrations for the RBs. Highlights: A new dynamic modelling method for predicting the time-varying plastic deformation at the spall edge is proposed. Dynamic impact force, total contact deformation, plastic deformation, and spall edge propagation rate are analyzed. Effects of the spall length, spall edge radius, external radial load, and rotor speed are studied.